Microglia are crucial regulators of neuro-immunity during central nervous system tuberculosis - Spanos, Jonathan Paul; Hsu, Nai-Jen; Jacobs, Muazzam (Frontiers in Cellular Neuroscience, 2015)
Mycobacterium tuberculosis (M. tuberculosis) infection of the central nervous system (CNS) is the most devastating manifestation of tuberculosis, with both high mortality and morbidity. Although research has been fueled by the potential therapeutic target microglia offer against neurodegenerative inflammation, their part in tuberculosis infection of the CNS has not been fully evaluated nor elucidated. Yet, as both the preferential targets of M. tuberculosis and the immune-effector cells of the CNS, microglia are likely to be key determinants of disease severity and clinical outcomes. Following pathogen recognition, bacilli are internalized and capable of replicating within microglia. Cellular activation ensues, utilizing signaling molecules that may be neurotoxic. Central to initiating, orchestrating and modulating the tuberculous immune response is microglial secretion of cytokines and chemokines. However, the neurological environment is unique in that inflammatory signals, which appear to be damaging in the periphery, could be beneficial by governing neuronal survival, regeneration and differentiation. Furthermore, microglia are important in the recruitment of peripheral immune cells and central to defining the pro-inflammatory milieu of which neurotoxicity may result from many of the participating local or recruited cell types. Microglia are capable of both presenting antigen to infiltrating CD4+ T-lymphocytes and inducing their differentiation - a possible correlate of protection against M. tuberculosis infection. Clarifying the nature of the immune effector molecules secreted by microglia, and the means by which other CNS-specific cell types govern microglial activation or modulate their responses is critical if improved diagnostic and therapeutic strategies are to be attained. Therefore, this review evaluates the diverse roles microglia play in the neuro-immunity to M. tuberculosis infection of the CNS.